The Poetry of Miqdar Ibn almukhtar Al-matamiri ( died 593 AH): A Collection , incension , and study - Adel Ismail Hassan Mahal Al-Jubouri, Dr. (lark, 2023)
The poet Miqdar bin almukhtar Al-matamiri (died 593 AH ) is one of the poets who were interested in poetics ( poetry) and contributed in the development of this kind. We know little about his life , he was one of the laurtuse . Historians  mentioned little about him and his poetry . I found some works referred by the poets of his time and in the dictionaries of literature though many of his poems are not available.  We could not find any anthology belongs to him or any collections in which his poetry was written . This was the incentive to step forward  to gather the fragments of these texts and poems to be studied scientifically. His works were collected from the references . They were enough to be published to rebirth his works and his collections that were lost as many of the Muslims works were lost previously. About (241) lines of poetry were collected , that deserve to be studied and make recension to explore his capacities in poetry and rhetoric potentials. The article was divided into two sections and a conclusion preceded by an introduction  in which the biography of the poet was mentioned. The first section was devoted to the most important themes . The second included the lines of his poetry. The article was conducted with the most important result .
Keywords: Al-matamiri , Miqdar , bin almukhtar , Poetry